2015
DOI: 10.12968/jowc.2015.24.2.73
|View full text |Cite
|
Sign up to set email alerts
|

Management of a patient with small-area burns, severe sepsis and superficial vein thrombosis

Abstract: None of the authors have any financial interest to declare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…All these Corynebacterium spp. can cause invasive disease in patients with compromised skin or mucosal barrier function (e.g., patients suffering from burn wounds or carrying intravascular devices) or in immunocompromised patients (e.g., diabetics and cancer patients) (7)(8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%
“…All these Corynebacterium spp. can cause invasive disease in patients with compromised skin or mucosal barrier function (e.g., patients suffering from burn wounds or carrying intravascular devices) or in immunocompromised patients (e.g., diabetics and cancer patients) (7)(8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%
“…Diabetes was among the predisposing factors. This pathogen has been known to cause wound infections earlier also [11,12]. Superti et al reported a case of C. striatum skin and soft tissue infection of a malignant skin lesion in a 27 y old male patient.…”
Section: Discussionmentioning
confidence: 99%
“…Thermal-crush injuries of the hand often involve severe composite injuries and defects of bones and soft tissues that require the bone and soft tissue reconstruction (6). Free tissues are usually used for reconstruction, especially free toe transplantation and free skin flap repair (7). Notably, an external fixation using Ilizarov external frame and bone transport technology is preferred to the reconstruction of bones and soft tissues in patients with thermal-crush injuries of the hand due to the fragile structure of the soft tissues of the hand (8).…”
Section: Introductionmentioning
confidence: 99%